Getting (Along) With the Guidelines: Reconciling Patient Autonomy and Quality Improvement Through Shared Decision Making. (July 2016) - Xu, Yan; Wells, Philip S.
Abstract : In past decades, stark differences in practice pattern, cost, and outcomes of care across regions with similar health demographics have prompted calls for reform. As health systems answer the growing call for accountability in the form of quality indices, while responding to increased scrutiny on practice variation in the form of pay for performance (P4P), a rift is widening between the system and individual patients. Currently, three areas are inadequately considered by P4P structures based largely on physician adherence to guidelines: diversity of patient values and preferences; time and financial burden of therapy in the context of multimorbidity; and narrow focus on quantitative measures that distract clinicians from providing optimal care. As health care reform efforts place greater emphasis on value-for-money of care delivered, they provide an opportunity to consider the other "value"—the values of each patient and care delivery that aligns with them. The inherent balance of risks and benefits in every treatment, especially those involving chronic conditions, calls for engagement of patients in decision-making processes, recognizing the diversity of preferences at the individual level. Shared decision making (SDM) is an attractive option and should be an essential component of quality health care rather than its adjunct. Four interwoven steps toward the meaningful implementation of SDM in clinical practice—embedding SDM as a health care quality measure, "real-world" evaluation of SDM effectiveness, pursuit of an SDM-favorable health system, and patient-centered medical education—are proposed to bring focus back to the beneficiary of health care accountability, the patient.